Psychosomatic aspects of diabetes mellitus - Repšytė, E.; Streikus, Z. (Psichologija, 1990)
Diabetes mellitus is commonly considered to be a disease that is incurable, but may be properly controlled. It is a kind of chronic psychosomatic disease, the management and self-care of which is presumed to be influenced greatly by the patients beliefs, emotions and his active participation in the treatment. Literature on psychosomatic aspects of diabetes is reviewed in the paper. The study suggests that patients with diabetes have a markedly increased trait and state anxiety, as well as neurotization. The very notable feature of these patients is an inadequate reaction to their disease, self-care, which doesn't show any changes during somatic-oriented medication.
Keywords: psychosomatic aspects; diabetus mellitus